1991
DOI: 10.1056/nejm199110243251704
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplantation Blood Transfusion Revisited

Abstract: Blood transfusion in which there is a common HLA haplotype or shared HLA-B and HLA-DR antigens induces tolerance to donor antigens. This finding may lead to the development of new strategies with which to induce tolerance for transplantation after blood transfusion. Perhaps transplant donors will be selected not only by HLA-antigen matching, but also on the basis of acceptable HLA-antigen mismatches associated with T-cell non-responsiveness induced by selected blood transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(54 citation statements)
references
References 18 publications
3
50
0
1
Order By: Relevance
“…However, the use of DSBT clinically has become less popular with the advent of calcineurin inhibitors and because a clear understanding of the mechanisms involved had remained elusive (11)(12). Recently, our group demonstrated in a rodent transplant model (in which DSBT alone induces tolerance) that Tregs operate (15).…”
mentioning
confidence: 99%
“…However, the use of DSBT clinically has become less popular with the advent of calcineurin inhibitors and because a clear understanding of the mechanisms involved had remained elusive (11)(12). Recently, our group demonstrated in a rodent transplant model (in which DSBT alone induces tolerance) that Tregs operate (15).…”
mentioning
confidence: 99%
“…The mechanism by which DLI induces operational transplantation tolerance remains elusive. The promotion of chimerism was suggested as a possible mechanism by which DLI or donor-specific transfusion modulates allogeneic immune responses and leading to graft acceptance (18). However, we did not identify donor leukocytes in the secondary lymphoid organs of DLI/anti-CD4-treated mice 30 days after xenotransplantation (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Donor-specific blood transfusion (DST) is a clinically and experimentally proven method to induce hyporesponsiveness and does not necessarily require additional immunotherapy [2][3][4][5][6]. However, the use of DST clinically has become less popular with the advent of calcineurin inhibitors and because a clear understanding of the mechanisms involved had remained elusive [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Donor-specific blood transfusion (DST) is a clinically and experimentally proven method to induce hyporesponsiveness and does not necessarily require additional immunotherapy [2][3][4][5][6]. However, the use of DST clinically has become less popular with the advent of calcineurin inhibitors and because a clear understanding of the mechanisms involved had remained elusive [4,6].In adult rats, long-term survival of MHC-incompatible vascularized allografts (heart or kidney) can be obtained by priming the recipients with donor blood cells [7,8]. We and others have shown that inhibition of early allograft rejection by DST mostly affects helper T cell functions [9][10][11] and requires intact resident dendritic cells at the time of transplantation [12].…”
mentioning
confidence: 99%